Komunikasi Pastoral dalam Penanganan Depresi - Widyasari, Yolantya; Tenie (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
Depression can happen anywhere, such as happened in Katingan Regency, Central Kalimantan Province. During 2022, there have been six cases of depression which caused all the victims to hang themselves and occurred at close intervals, so the district government requires religious figures to provide spiritual guidance to the community to reduce cases of depression in the area. And one of the churches that has implemented guidance is GKE Hosana Buntut Bali, Katingan Regency. This study aims to describe the condition of people with depression and the implementation of pastoral communication in reducing depression rates, especially in GKE Buntut Bali, Katingan Regency. This research used descriptive qualitative method. Data collection techniques used, namely observation, interviews, documentation studies and triangulation techniques. The results of this research found that depression is caused by family problems, economic problems, and even health problems. Furthermore, in implementing Pastoral Communication, the Pastor knows the communicant, maintains openness, uses language that is easy to understand, uses analogies or relevant examples, and maintains solemnity and attention. Thus, the pastoral care carried out produces a healing function, a supporting function, and a complete function that is oriented towards the physical, mental, social and spiritual aspects of the sufferer.